Students' Perceptions of Academic Efficacy and School Supports: A Mismatch with School Demographics - Jason T Hurwitz; Kris Bosworth; Regina Deil-Amen; Cecilia Rios-Aguilar; J. Robert Hendricks; Eliane B. Rubenstein-Avila (Arizona State University, 2015)
This exploratory study aimed to (a) identify students beliefs about their abilities and school environments to achieve their college and career aspirations, (b) group schools by students perceptions, and (c) contrast this grouping with grouping by school-level demographics. This secondary analysis examined items from the County Youth Survey administered to 11th-graders (N = 3,751) at 17 local schools. School size and racial and socioeconomic statistics comprised the publicly available data. Principal components analysis identified 17 college and career readiness items representing two dimensions of student perceptions: School Supports and Academic Efficacy. Cluster analysis revealed that schools grouped by these dimensions differed substantially from the demographic groupings.